2006
DOI: 10.1074/jbc.m604869200
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Binding and Conformational Dynamics in the Odorant-binding Protein

Abstract: In mammals, the olfactory epithelium secretes odorantbinding proteins (OBPs), which are lipocalins found freely dissolved in the mucus layer protecting the olfactory neurons. OBPs may act as passive transporters of predominantly hydrophobic odorant molecules across the aqueous mucus layer, or they may play a more active role in which the olfactory neuronal receptor recognizes the OBP-ligand complex. To better understand the molecular events accompanying the initial steps in the olfaction process, we have perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 51 publications
4
47
0
2
Order By: Relevance
“…Although occluded from the bulk water, the binding cavity showed transient openings, notably at the junction between loop1 and strands D and E of the b-barrel [19]. Unconstrained [20] or constrained [21] molecular dynamics simulations observed the binding or unbinding of odorants through the opening of this part of the protein, confirming that it is the main access from the bulk to the binding cavity. Gratifyingly, the crucial role of a highly conserved tyrosine residue (Y82) initially pointed out in the simulations was experimentally confirmed afterward [13].…”
Section: Molecular Modeling Of Obpsupporting
confidence: 53%
“…Although occluded from the bulk water, the binding cavity showed transient openings, notably at the junction between loop1 and strands D and E of the b-barrel [19]. Unconstrained [20] or constrained [21] molecular dynamics simulations observed the binding or unbinding of odorants through the opening of this part of the protein, confirming that it is the main access from the bulk to the binding cavity. Gratifyingly, the crucial role of a highly conserved tyrosine residue (Y82) initially pointed out in the simulations was experimentally confirmed afterward [13].…”
Section: Molecular Modeling Of Obpsupporting
confidence: 53%
“…Further, it has been shown with the chip based surface plasmon resonance technique that the OBP is able to modulate the activity of olfactory receptors (Vidic et al, 2008). Some evidence for subtle conformational changes in rat and porcine OBPs after ligand binding has been obtained in molecular dynamics studies wherein opening of the -strand pair was observed (Hajjar et al, 2006). These structural dynamics of OBPs might be essential for recognition of the OBP-ligand complex by the olfactory receptor.…”
Section: Odorant-binding Proteinsmentioning
confidence: 95%
“…El mucus nasal posee proteínas olfatorias ligando (OBP), las que protegen el epitelio del daño causado por el estrés oxidativo, removiendo los componentes citotóxicos del mucus nasal. También poseen funciones olfatorias, entre las cuales se encuentran: ser transportadoras de moléculas volátiles y ligandos hidrofóbicos a través de la capa acuosa de mucus hacia el receptor, unir varias moléculas odorantes, juegan un rol en el reconocimiento del complejo ligando-OBP con el receptor neuronal, contribuir a amplifi car la señal olfatoria y participar en la remoción de los odorantes en el receptor para el cese de las señales olfatorias 11,12 .…”
Section: Neuroepitelio Olfatoriounclassified